2012
DOI: 10.1039/c2mt00146b
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium exposure disrupts elemental homeostasis in Caenorhabditis elegans

Abstract: Aluminium (Al) is highly abundant in the environment and can elicit a variety of toxic responses in biological systems. Here we characterize the effects of Al on Caenorhabditis elegans by identifying phenotypic abnormalities and disruption in whole-body metal homeostasis (metallostasis) following Al exposure in food. Widespread changes to the elemental content of adult nematodes were observed when chronically exposed to Al from the first larval stage (L1). Specifically, we saw increased barium, chromium, coppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…ICP analysis was conducted as previously described 37 . Briefly, synchronized populations of arrested L1s were grown en masse (25,000-40,000 worms) at 25°C to induce sterility in the temperature-sensitive mutant, spe-9(hc88) .…”
Section: Methodsmentioning
confidence: 99%
“…ICP analysis was conducted as previously described 37 . Briefly, synchronized populations of arrested L1s were grown en masse (25,000-40,000 worms) at 25°C to induce sterility in the temperature-sensitive mutant, spe-9(hc88) .…”
Section: Methodsmentioning
confidence: 99%
“…Elemental content was normalized to the dry weight of the tissue. Quality control and analytical procedures were performed as previously described (33). Further dilutions of the samples were used where necessary to obtain results for highly abundant elements.…”
Section: Studymentioning
confidence: 99%
“…Although the physiological requirement for Al has yet to be defined, it has been posited that Al may have an etiopathogenic role in neurodegenerative diseases (Halatek et al, 2005). Studies with Al in the form of AlCl 3 , Al(NO 3 ) 3 , or Al 2 (SO 4 ) 3 identified phenotypic abnormalities, including toxic effects on lifespan, body size, development, reproduction, locomotion, behavioral plasticity, and memory in the worm (Wang et al, 2009; Page et al, 2012). Additionally, Page et al showed changes in elemental composition of whole worms exposed to Al, noting a significant increase in multiple metals and ensuing oxidative stress (Ba, Fe, Cr, and Cu), hypothesizing that altered levels of these elements contributed to the aforementioned phenotypes seen in chronic Al toxicity (Page et al, 2012).…”
Section: Techniques For Studying Neurodegeneration In C Elegansmentioning
confidence: 99%